The Old Stone House Site of Olak Kemang as a Source for Learning Indonesian History during the Age of Islamic Influence in Senior High Schools - Pauzan J; Hardina Hardina (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To find out how far the Old Stone House site has been used as a learning resource for Indonesian history under the influence of Islam for education and students. Methodology: The method used is a qualitative method with a descriptive text approach. As for data collection techniques using qualitative data collection techniques in the form of interviews, observation and documentation. Main Findings: The results of the study show that there are several heritage buildings of the Jambi sultanate at the time of spreading Islamic teachings and during the Dutch colonial period which had Indonesian history during the Islamic Influence era. Novelty/Originality of this study: The Islamic legacy in the Olak Kemang sub-district is very important to be used as a learning resource so that learning Indonesian history under Islamic influence is more enjoyable, challenging, and meaningful.